2013
DOI: 10.1007/s11552-012-9491-4
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Knotless Flexor Tendon Repair Using Large-Diameter Unidirection Barbed Suture

Abstract: Purpose In traditional flexor tendon repairs, suture knots can be sites of weakness, impair tendon healing, stimulate an inflammatory response, and increase the bulk of the tendon repair. Because of this, there has been an increased interest in knotless flexor tendon repair using barbed suture. Since knots are not required, it may be possible to increase the strength of the tendon repair by using a large-diameter barbed suture. The purpose of this study was to biomechanically compare a traditional four-strand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
11
1
Order By: Relevance
“…Contrary to our findings which showed the barbed suture to be biomechanically equivalent to the conventional monofilament sutures, there are studies which have found them to be inferior and superior to the conventional sutures (9,(11)(12)(13)(14). Trocchia et al (11) reported that Kessler tendon repair done with a 2/0 barbed suture was biomechanically inferior to the repair done with a 3/0 non-absorbable braided conventional suture.…”
Section: Discussioncontrasting
confidence: 98%
“…Contrary to our findings which showed the barbed suture to be biomechanically equivalent to the conventional monofilament sutures, there are studies which have found them to be inferior and superior to the conventional sutures (9,(11)(12)(13)(14). Trocchia et al (11) reported that Kessler tendon repair done with a 2/0 barbed suture was biomechanically inferior to the repair done with a 3/0 non-absorbable braided conventional suture.…”
Section: Discussioncontrasting
confidence: 98%
“…Their results demonstrate a statistically significant higher load to failure for the barbed suture group as compared to the unbarbed group [18].…”
Section: Positive Resultsmentioning
confidence: 94%
“…Tendons were preloaded to 3 N and then stretched linearly by the Instron™ machine (Model 8521; InstronCorp., Canton, MA) at a rate of 20 mm/min until failure, similar to protocols used in similar studies. 10,13,27,28 Trials were recorded using a digital video camera and a ruler was positioned next to the tendon to provide a reference of length.…”
Section: Methodsmentioning
confidence: 99%
“…23 Barbed suture tenorrhaphy theoretically allows smoother gliding under pulleys by decreasing cross-sectional area under load, better load distribution along the entire suture length, and improved tendon flow by reducing constricting forces. 10 10,11,13,14,18,19,23,27,28 but minimal data exist in comparing the barbed sutures with each other. The purpose of this study was to determine if any differences exist between conventional nonbarbed, V-Loc™, and Stratafix™ barbed suture core repairs in gap resistance or ultimate tensile strength in an established biomechanical ex vivo model of flexor tenorrhaphy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation